Friday

July 25, 2014

July 25, 2014

Posted by **jean** on Saturday, July 5, 2008 at 7:14pm.

6x^2-7x=3

We have to move the 3 to the left so it becomes

6x^2-7x-3=0

6x^2-7x-3=0 this makes this a quadratic equations 6*x^2-7*x-3=0 and has the answer of 1.5,-0 so

0=0

solution is x=1.5, x= -0.3333333333

- algebra -
**DrBob 222**, Saturday, July 5, 2008 at 7:23pmI don't get the 0=0 step but your solution is correct for x = 1.5 and x = -0.3333.

- algebra -
**jean**, Saturday, July 5, 2008 at 7:27pmso can you please show me what i am doing wrong with this?

- algebra -
- algebra -
**DrBob 222**, Saturday, July 5, 2008 at 7:38pmI don't know that you did anything wrong. How did you solve the quadratic? Did you use the quadratic formula?

**Related Questions**

Pre-Algebra - Is this correct? If I'm mistaken, please correct it for me, and ...

PLease Help Me IN Math - Problem: 25-x^2 6 ------ * --- 12 5-x What I Got: 5-x...

Maths - There was a question: A gallon jug of milk is 3/4 full. After breakfast...

Quadratic equation.. - Hi Can anyone tell me if this is correct X Sq - 4x - 16...

college algebra - (x-3)^2+(y-2.5)^2=7.25 Make a new equation that shifts up 1 ...

college algebra - (x-3)^2+(y-2.5)^2=7.25 Make a new equation that shifts up 1 ...

Algebra - 1. √(9y - 196) + √196 = √49 My work: I squared all 3...

algebra - Solve for s in this equation. Depreciation. D=C-s/n This is my answer ...

math - I don't want to get this wrong for this homework that i have to turn in ...

URGENT Spanish help please. - ok in the example it shows: ¿Comprendes espanol? ...